2010
DOI: 10.1007/s11434-009-0693-2
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of thermocapillary convection and evaporation effect in a liquid layer when the evaporating interface is open to air

Abstract: The coupling mechanism of thermocapillary convection and evaporation effect in evaporating liquids was studied experimentally. The experiments were carried out to study a thin evaporating liquid layer in a rectangular test cell when the upper surface was open to air. By altering the imposed horizontal temperature differences and heights of liquid layers, the average evaporating rate and interfacial temperature profiles were measured. The flow fields were also visualized by PIV method. For comparison, the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…The measurement indicated that the layer thickness decreased approximately linearly with time (Zhu and Liu 2010), which partly supported the hypothesis of quasi-stable evaporating condition in present experiments. Under the above quasi-stable condition, we performed the measurements as soon as possible, and the liquid layer thickness in one experiment was assumed to be approximately constant with the evaporation-induced decrease of 5 %.…”
Section: Experimental Setup and Measurement Techniquessupporting
confidence: 89%
See 2 more Smart Citations
“…The measurement indicated that the layer thickness decreased approximately linearly with time (Zhu and Liu 2010), which partly supported the hypothesis of quasi-stable evaporating condition in present experiments. Under the above quasi-stable condition, we performed the measurements as soon as possible, and the liquid layer thickness in one experiment was assumed to be approximately constant with the evaporation-induced decrease of 5 %.…”
Section: Experimental Setup and Measurement Techniquessupporting
confidence: 89%
“…Although the evaporating was also strengthened, synchronous enhancing thermocapillary flow could bring more heat energy to compensate the heat loss taken by evaporation. Eventually, the interfacial temperature was always higher in deeper liquid layer at center point (Zhu and Liu 2010). As we mentioned above, the temperature discontinuity was strongly related to the temperature at the liquid-vapor interface.…”
Section: Temperature Discontinuity Distribution Along the Center Linementioning
confidence: 73%
See 1 more Smart Citation
“…In both of these cases, evaporation is therefore at least somewhat balanced by condensation, and phase change occurs in the presence of air at ambient pressures. Zhu and Liu 16 instead studied convection in a L = 4 cm and W = 8 cm layer of 0.65 cSt silicone oil subject to ∆T ≤ 14 • C with an initial depth h = 0.2 cm where the interface was open to the surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…f a c e t e m p e r a t u r e ( ℃ ) X ( m m ) P r e s e n t s i m u l a t i o n Z h u a n d L i u ( 2 0 1 0 ) Comparison of the surface temperature profile between the present numerical simulation and the experimental measurement by Zhu and Liu[41] …”
mentioning
confidence: 93%